MORALITAS PIMPINAN DALAM PERSPEKTIF ISLAM - Yazid, Syamsurizal (Jurnal Bestari, 2001)
According to islam, morality is very important in human life for all mankind in general and for their ruler n leader in particural. Prophet muhammad Peace be Upon Him (PBUH) said: ? I was only sent to complete good morality? . it?s not an apology if it is said that islam in the only religion of the world that has clear concept of morality. The morality of islam is based on the revelations of god. Holy Quran and Hadits contain many teachings of morality. The range of morality in islam so inclusive and integrative that is combines at once faith in God, religious rites , spritual observances, social conduct, decision making, intellectual pursuits, habit of consumptions, manner of speech, and all other aspect of human life. All the Muslim, have to manifest good values in these rites in their daily life. The rules and the leader must have good morality if they want to be success in fulfilling their tasks.